Poly(2,5-Benzimidazole) as a membrane material for solvent dehydration: effect of bound methanesulfonic acid - Alladi, Lavanya; Lele, Ashish K.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2025)
Towards addressing issues of solvent stability of polymeric membrane materials for pervaporation (PV), this work investigates thermochemically robust poly(2,5-benzimidazole) (ABPBI) bound with methane sulfonic acid (MSA) for solvent dehydration, for the first time to our knowledge. Phase inversion membranes with and without bound-MSA were prepared, thermally treated at different temperatures up to 350 degrees C, and analyzed for physical and pervaporation properties. The physical characterizations (FTIR, WAXD, TGA, XPS, SEM, and EDX) and sorption analysis were performed using flat sheet membranes, whereas hollow fiber membranes were used for the pervaporation analysis with chosen solvents (alcohols and two polar aprotic solvents). Physical characterizations established the presence of MSA and the nonporous, dense nature of membranes, irrespective of their treatment temperatures. The sorption of pure solvents in the membrane is primarily affected by thermal treatment of the membranes. The pervaporation analysis was performed using different solvent: Water feed compositions. Using 85:15 as the feed, the average separation factors for dehydration of isopropanol, acetonitrile, and N,N-dimethylformamide (DMF) were 393, 213, and 185, respectively, with an appreciable ``pervaporation separation index.'' The long-term membrane performance till 360 h was analyzed to shed light on practical applicability.
Keywords: membranes; separation techniques; synthesis and processing techniques

Poly(2,5-Benzimidazole)-based flat sheet membranes: investigating effects of dope solvent and membrane heat treatment on forward osmosis and acid enrichment performances - Somkuwar, Nitin C.; Thorat, Nitin M.; Ambade, Ashootosh; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2026)
The present work investigates two methods for preparing defect-free, symmetric membranes of the thermochemically robust polymer, poly(2,5-benzimidazole) (commonly known as ABPBI) for forward osmosis (FO), a growing technology for niche separations. The obtained polymer and membranes were analyzed for physical properties of significance. The FO analysis was performed using three salt solutions, viz., sodium chloride (NaCl), magnesium chloride (MgCl2), and sodium sulfate (Na2SO4). The effects of casting methodology (solvents present in the dope), membrane heat treatment, draw solution concentration, long-duration analysis, and FO-assisted enrichment of organic acids were evaluated. Some of the membranes exhibited extremely low reverse salt flux (RSF), which conveys the novelty of these membranes. Some of these membranes were analyzed using a high draw solution (DS) concentration (4 mol L-1) to enhance water flux and further employed to enrich organic acids. The aqueous acetic and methacrylic acid concentrations were enriched from 4.89 and 2.93 mol L-1 to 11.88 and 10.01 mol L-1, respectively. These results demonstrate an unmet need of concentrating methacrylic acid (a temperature-sensitive compound possessing a double bond). The present work demonstrates the potentials of ABPBI-based symmetric, thin membranes for FO and their industrial applicability for the first time.
Keywords: Applications; membranes; separation techniques